The Impact of Product Promotion and Innovation on Purchase Decisions at Prices as Intervening Variables - Joe Eklesia Apostolos Sujarwo; Eko Suseno Hendro Riyadi Matruty (International Journal of Social Science and Business, 2021)
Technological developments, especially in the field of digital marketing, in the new normal era this time had become a phenomenon that is no longer rare in society to carried out various activities, such as buying and selling online. The development of digital marketing in the new normal era is currently very fast. Several online shops that use digital marketing techniques such as Shopee and Tokopedia. This study aims to analyzed the effect of promotion and product innovation on purchasing decisions with price as an intervening variable. The research method used purposive sampling technique where the data is examined using measurements by considering individual choices. The sample collection used a questionnaire, and the number of samples used is 100 respondents. The analysis technique used multiple linear regression and multiple test. The results showed that the first hypothesis did not have a significant influence between the promotional variables on purchasing decisions. While the second hypothesis there is a significant influence between product innovation variables on purchasing decisions. Furthermore, the third and fourth hypothesis of the price variable mediate the relationship between promotion and product innovation on purchasing decisions.